PERAN IBU RUMAH TANGGA PEDAGANG SAYUR UNTUK MENINGKATKAN PEREKONOMIAN KELUARGA DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus : Pasar Mayang Mangurai Nipah Panjang II) - Sella Rahmadanti; Putri Apria Ningsih; Ahmad Syahrizal (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In general, men fulfill the family's needs, but because the husband's income is limited, the wife plays a role in helping to improve the family's economy by trading vegetables from market to market. The formulation of the problem in this research is what is the role of housewives who sell vegetables in improving the family economy at Mayang Mangurai Market, what is the Islamic economic view of the role of wives in improving the family economy at Mayang Mangurai Market. This research uses qualitative research methods. Data was taken from in-depth interviews and observations. The research results show that housewives' understanding of family economic management is very simple. Women's involvement in family economic activities is to help their husbands in meeting family needs. Women at work certainly have an impact on the order of life. Then the Position of Women in Supporting the Family. Islam does not burden women to earn a living. There are also Islamic and state policies in providing protection for working women.